RELIGIOUS EXPERIENCE OF THE CHRISTIAN MUKKUVA COMMUNITY: Insights and Challenges from the Coastal Context - Mathew, P T (Journal of Dharma, 1999)
Christian life and practice present before us a living paradox.The Christian tradition, on the one hand, is deeply rooted in the subaltern soil of ancient Israel and of the, Roman empire; the dominant mode of religious thought and theological discourse in the contemporary Church, on the,other hand, keeps a distance from the religious experience of subaltern peoples and groups. This paradox is evident in the pronouncements of the magisterium, in the articulation of theological thinking, and in the training programme of Church functionaries. This paper has to be situated within this paradox.